A Novel Robot Tool Manipulation Method for Battery Degumming Task - Jiangtao, Xiao; Yu, Xie; Renpeng, Wang; Jinhui, Zhang; Wei, Zhou; Yi, Zhang (2024 7th International Symposium on Autonomous Systems (ISAS), 2024)
Battery degumming is an important part of electric vehicle battery assembly. However, uncertainties in the location and amount of adhesive overflow, coupled with the uneven nature of degumming surfaces, make traditional robot position control modes inadequate in such a scenario. In this paper, a novel robot tool manipulation strategy is presented to solve the issues. First, a task-space impedance control teamwork is employed to achieve the adaptive adjustment of the robot degumming force and the tool contact following the working surface. Then a tool degumming force identification method is introduced, which works as a real-time degumming force feedback for impedance control. Experiments are conducted on a 6-DoF manipulator for the validation.